PSYCHOLOGICAL ANALYSIS OF NICOLE BARBER IN DEALING WITH CONFLICT IN MARRIAGE STORY MOVIE - Swecandari Wake, Yosephina Feolita (LPPM Universitas Dhyana Pura, 2021)
ABSTRACTIn a movie, there are intrinsic elements and extrinsic elements. One of the elements thatmakes a film interesting is the conflict and the characters. Conflicts that occur can be inthe form of physical or psychological conflicts. A person's psychology can affect theemergence of a conflict in a character and can also affect how a character can solve theirproblem. The undergraduate thesis entitled